2020
DOI: 10.1021/acsami.0c06054
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antibiofilm Nanocomposites: Ag/Cu Bimetallic Nanoparticles Synthesized on the Surface of Graphene Oxide Nanosheets

Abstract: There are numerous issues associated with bacteria, particularly biofilms, which exhibit a strong resistance to antibiotics. This is currently considered an urgent global issue owing to the lack of effective treatments. Graphene oxide (GO) nanosheets are twodimensional carbon materials that are available as a substrate for metal nanoparticles and have a lower release rate of metal ions than free metal nanoparticles by regulating the oxidation of metal nanoparticles, which is known to reduce the cytotoxicity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
(64 reference statements)
1
34
0
Order By: Relevance
“…8 Cheng et al 9 loaded ceria nanoparticles on graphene nanocomposites and observed enhanced antibacterial properties against E. coli and Staphylococcus aureus because of numerous reactive oxygen species, which originated from the excellent photoinduced electrons and holes' separation ability in that composite. Similar results were obtained by Jang et al 13 to remove several bacterial species and biofilms by bimetallic Ag/Cu nanoparticles decorated on GO flakes because of the two metal ions' release over time. Moreover, Akhavan and Ghaderi 19 suggested that the sharp edges of the sheets are responsible for cell rupture.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…8 Cheng et al 9 loaded ceria nanoparticles on graphene nanocomposites and observed enhanced antibacterial properties against E. coli and Staphylococcus aureus because of numerous reactive oxygen species, which originated from the excellent photoinduced electrons and holes' separation ability in that composite. Similar results were obtained by Jang et al 13 to remove several bacterial species and biofilms by bimetallic Ag/Cu nanoparticles decorated on GO flakes because of the two metal ions' release over time. Moreover, Akhavan and Ghaderi 19 suggested that the sharp edges of the sheets are responsible for cell rupture.…”
Section: Introductionsupporting
confidence: 87%
“…Not only was it harmless to mammalian cells, but it was toxic enough to inhibit the growth of pathogenic bacteria such as Escherichia coli. , Later, graphene and its derivatives with and without functionalization and hybrid components such as Ag and Au were tested for bactericidal effects. Considering the high rate of hospital-acquired infections (the sixth leading cause of death in hospitals), G/GO antibacterial agents seem to be promising candidates to stop bacteria’s proliferation in such environments. …”
Section: Introductionmentioning
confidence: 99%
“…48 Moreover, another study has documented that Ag/Cu/GO nanocomposite inhibited the biolm formation of P. aeruginosa at the concentration which was harmless to human cells. 49 Our ndings clearly show the ability of TiO 2 -NPs in inhibiting the biolms of both Gram +ve and Gram Àve bacteria.…”
Section: Microscopic Analysis Of Biolms Inhibition On Glass Surface Usingmentioning
confidence: 70%
“…The nanosystem revealed similar efficacy against S. aureus biofilm with commercial Acticoat Flex 3 (a silver-coated dressing) in an engineered tissue infection skin model. Copper was combined with silver to form bimetallic nanoparticles for antibiofilm treatment [122]. The average diameter of the nanoparticles was about 7 nm.…”
Section: Topically Applying Nanoparticles To Treat Cutaneous Biofilms 61 Metallic Nanoparticlesmentioning
confidence: 99%